Literasi Asuransi Guna Mengoptimalkan Kewirausahaan - Indah Sulistyowati , Rini; Januarta, Ganda; Moeljono, Moeljono; Souisa, Johanis (Literasi Jurnal Pengabdian Masyarakat dan Inovasi, 2025)
Entrepreneurship is a key driver of the local economy. Businesses, particularly those in the micro, small, and medium enterprises (MSMEs) sector, play a crucial role in creating jobs, increasing family incomes, and driving local economic growth. However, despite this significant potential, many businesses still face various risks that can hinder or even halt their operations, such as fire, loss of goods, accidents, or health problems.MSMEs remain relatively low aware of the importance of protecting their businesses through insurance. Many don't understand the benefits of insurance, consider it an additional burden, or aren't even aware that affordable insurance products specifically designed for small businesses exist. This leaves MSMEs highly vulnerable to unexpected risks that can result in significant losses, both financially and operationally.Through this community service activity held in Kemijen Village, East Semarang, we strive to provide insight and knowledge to MSMEs, the general public, and business owners so they have adequate insurance literacy. This activity helps the community understand the basic concepts of insurance, the types of insurance available, and the benefits they can obtain. With better knowledge, the community will be wiser in managing their finances and can consider insurance as part of their family's financial planning